THE FUNCTION OF RITUAL IN TRADITIONAL SOCIETY - Naumkina V. V. (Scientific Journal of Pedagogy and Economics, 2019)
The aim of the study is to analyze the functions of the ritual in the conditions of customary law. On the basis of historical analysis and dialectical approach the main functions of traditional rituals, as well as the reasons for the refusal of society from the rituals in the distribution of written law are highlighted. The study analyzes the specifics of the rite as an element of customary law. The rite is discussed in conjunction with custom, as an essential condition for the validity of custom. It is concluded that customary law as an institution is represented by a set of elements, each of which performs certain functions and ensures the existence of the entire system. Features of act and conservation of customs became the reason of the quantitative and qualitative development of the rites. With the loss of regulatory values of customs, society begins to abandon the rites.